Iterative Voting under Uncertainty for Group Recommender Systems (Research Abstract) - Naamani-Dery, Lihi (Proceedings of the AAAI Conference on Artificial Intelligence, 2021)
Group Recommendation Systems (GRS’s) assist groups when trying to reach a joint decision. I use probabilistic data and apply voting theory to GRS’s in order to minimize user interaction and output an approximate or definite “winner item